Identifikasi Pemborosan dalam Proses Produksi Pakan Ternak Ayam di PT.XYZ dengan Menggunakan Metode Value Stream Analysis Tools (VALSAT) - Adityah Maulana; Achmad Misbah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to identify various types of waste in the chicken feed production process at PT. XYZ and provide improvement recommendations to reduce production costs. The method used is the Value Stream Analysis Tools (VALSAT) to map and analyze the value stream in the production process. This research includes direct observation and data analysis to find the main wastes. The results show seven main types of waste in the chicken feed production process: waiting time, unnecessary movements, product defects, excess inventory, inefficient processes, overproduction, and transportation. However, the research encountered several challenges, such as data limitations and difficulties in collecting accurate data. The largest waste found was excess inventory, with an average score of 9.13. This research provides clear insights into areas in the production process that require improvement. The implementation of the improvement recommendations is expected to increase the company's efficiency and productivity. Despite facing some challenges, the use of VALSAT proved effective in identifying and analyzing waste. It is hoped that the provided improvement recommendations can reduce waste and enhance operational efficiency at PT. XYZ.